Patient radiation doses in paediatric interventional cardiology procedures: a review. (28th November 2016) - Harbron, R W; Dreuil, S; Bernier, M-O; Pearce, M S; Thierry-Chef, I; Chapple, C-L; Baysson, H
Abstract: A large number of investigations into the radiation doses from x-ray guided interventional cardiology procedures in children have been carried out in recent years. A review was conducted of these studies, gathering data on kerma area product ( P KA ), fluoroscopic screening time (FT), air kerma, and estimates of effective dose and organ doses. The majority of studies focus on P KA and FT with no estimation of dose to the patient. A greater than ten-fold variation in average P KA was found between different studies, even where data were stratified by patient age or weight. Typical values of P KA were 0.6–10 Gy · cm 2 (<1 year/10 kg), 1.5–30 Gy · cm 2 (1–5 years), 2–40 Gy · cm 2 (5–10 years), 5–100 Gy · cm 2 (10–16 years) and 10–200 Gy · cm 2 (>16 years). P KA was lowest for heart biopsy (0.3–10 Gy · cm 2 for all ages combined) and atrial septostomy (0.4–4.0 Gy · cm 2 ), and highest for pulmonary artery angioplasty (1.5–35 Gy · cm 2 ) and right ventricular outflow tract dilatation (139 Gy · cm 2 ). Most estimates of patient dose were in the form of effective dose (typically 3–15 mSv) which is of limited usefulness in individualised risk assessment. Few studies estimated organ doses. Despite advances in radiation protection, recent publications have reported surprisingly large doses, as represented by P KA and air kerma. There is little indication of a fall in these dose indicators over the last 15 years. Nor is there much suggestion of a fall in doses associated with the use of flat panel detectors, as opposed to image intensifiers. An assessment of the impact of radiation dose in the context of overall patient outcome is required.